Russian Federation : Diagnostic Review of Consumer Protection in Financial Services, Volume 1. Key Findings and Recommendations - World Bank (Washington, DC, 2013)
This paper is a pilot diagnostic review of consumer protection in financial services in the Russian Federation. The review examines financial services in Russia, but also emphasizes the need for a set of good practices, or benchmarks, for use in reviewing consumer protection in financial services in any jurisdiction. This work will prove helpful to the international community, and those in emerging markets. The review finds that most people in Russia do not consider themselves financially literate, and have little understanding of their rights as consumers. The review's objectives are to conduct a review of the existing rules and practices in Russia, compared to international good practices on consumer protection in financial services; provide recommendations on ways to improve consumer protection in financial services in Russia; and refine a set of good practices prepared by the World Bank for assessing consumer protection in financial services. As part of the conclusion, methods for better financial education for consumers, are provided